Poultry Litter Solid State Anaerobic Digestion: Effect of Digestate Recirculation Intervals and Substrate/Inoculum Ratios on Process Efficiency - Marchioro, Vanessa; Steinmetz, Ricardo L. R.; do Amaral, Andre C.; Gaspareto, Taís C.; Treichel, Helen; Kunz, Airton (Frontiers in Sustainable Food Systems, 2018)
This study evaluated the effect of the substrate:inoculum ratio and digestate recirculation conditions on the biogas and methane yield, free ammonia concentration and solid phase agronomic quality (after treatment) of poultry litter solid state anaerobic digestion (SSAD). Experimental tests were conducted using a central composite design (2²), with four trials at the factorial points and three at the central points, using poultry litter as substrate that was collected after 12 cycles of broiler production (TS 76% (w.w-1)). Three laboratory-scale reactors containing 3 kg of poultry litter each were operated at mesophilic conditions (37°C) and seven experimental runs were performed at retention time of 30 days each. There were three substrate:inoculum ratios (1:1; 1:1.66 and 1:3) and three daily recirculation intervals (2, 3 and 4 times per day), and each recirculation event lasted 15 min. The highest biogas and methane yields were183 LNbiogas.kgVSadd-1and 74 LNmethane.kgVSadd-1, respectively, and they were obtained at the substrate:inoculum ratio of 1:3 with a digestate recirculation frequency of four times a day. Digestate recirculation was the variable that influenced the concentration of free ammonia; the most frequently recirculated tests had lower concentrations (below 60 mgNH3.L-1). After the SSAD process, we identified a transfer of nutrients (N, P, K) from the solid phase to the liquid phase. The nutrient concentrations in the solid phase (Nout = 11 g.kg-1, Kout=5 g.kg-1 and Pout = 7 g.kg-1) indicated that the digested poultry litter still has potential for use in fertilization. In this study, it was estimated that 90 m³biogas.tonspoultrylitter-1 was generated using SSAD. Whereas 100 tons of poultry litter are produced after 12 production cycles, the biogas generation capacity reaches 9,000 m³/year. In this scenario, farmers can use biogas from poultry litter SSAD as an additional source of energy.n capacity reaches 9000 m³/year. In this scenario, farmers can use biogas from poultry litter SSAD as an additional source of energy.